Stent Selection for Endoscopic Ultrasound-Guided Drainage of Pancreatic Fluid Collections: A Multicenter Study in China - Hui Lin; Xian-Bao Zhan; Si-Yu Sun; Xiu-Jiang Yang; Zhen-Dong Jin; Duo-Wu Zou; Zhao-Shen Li (Gastroenterology Research and Practice)
Aims. We attempted to establish some guidelines for the selection of transmural stents during endoscopic drainage of PFCs by retrospective review of the clinical data obtained from three tertiary hospitals. Patients and Methods. Clinical data of 93 patients with attempted endoscopic drainage of symptomatic PFCs were obtained through chart review and prospective follow-up. Results. Treatment success for acute pseudocyst (n=67), chronic pseudocyst (n=9), and WOPN (n=17) was 95.3%, 100%, and 88.2%, respectively (P=0.309). Clinical success for single-stent drainage was 93.9% (46/49) versus 97.4% (37/38) for multiple-stent drainage (P=0.799). Secondary infection for single-stent drainage was 18.4% (9/49) versus 5.3% (2/38) for multiple-stent drainage (P=0.134). Secondary infection for stent diameter less than or equal to 8.5 F was 3.4% (1/29) versus 17.2% (10/58) for stent diameter larger than or equal to 10 F (P=0.138). Conclusion. EUS-guided transmural drainage is an effective therapy for PFCs. Single-stent transmural drainage of PFCs is enough and does not seem to influence clinical success. The number or diameter of stents does not seem to be associated with secondary infection.